The Value of Character Education in the Novel Shoes Dahlan and Its Relevance to Indonesian Language Learning in Elementary Schools - Rika Rahayu; Rukayah Rukayah; Peduk Rintayati (AL-ISHLAH: Jurnal Pendidikan, 2022)
The purpose of this study was to determine the value of character education in the Novel Shoes Dahlan by Khrisna Pabichara. The research method uses a descriptive qualitative approach. The results of this study are that there are character education values in the form of (1) hard work in the form of parents having a hard work spirit to meet the needs of their children, as well as a child having a hard work spirit to achieve goals with their sweat, (2) independent in the form of not being too dependent on others, (3) discipline in the form of parents training their children about discipline. The child instills discipline in his daily life, (4) nationalist and (5) religious in the form of always praying before doing something. The relevance of character education in Indonesian is that creative literary works are born from the art of language and are likened to a description of human sociocultural life. Literary works can describe human life in various forms. The values possessed by literary works are accepted and understood by the reader, which will indirectly provide a picture of the reader's attitude and personality. Literature not only has a role in inculcating noble character but also has a role in character building since childhood.